Livelihoods and survival strategies pursued by international return migrants in Addis Ababa, Ethiopia - Abinet Fulasa Chinkilo; Teferee Makonnen Kassa; Temesgen Tilahun Teshome (Cogent Social Sciences)
In Ethiopia as far as the livelihood and survival strategies pursued by international returnees is concerned, such scientific study is scanty or non-existent. The study was devoted to explore the livelihoods and survival strategies chased among the returnees in Addis Ababa to provide scientific evidences and insights for decision making and future intervention efforts. Data were collected from 402 randomly drawn sample returnees via a cross-sectional survey. The supplementary data were collected from purposively selected focus group discussion and semi-structured interview participants. Descriptive statistics and Ordinal Logistic Regression Model (OLRM) were employed to analyze the data. The study revealed that while unemployment was found to be the most categorized livelihood strategy by which returnees were hallmarked and rated above the scale mean on the three-point likert scale (mean = 2.18, Standard Deviation/SD = 0.91); wage-employment and self-employment were rated below the scale mean (mean = 1.41, SD = 0.61; and mean = 1.39, SD = 0.56) respectively, which reflects that majority of the study population weren’t involved in livelihood strategies common in urban settings. OLRM results confirmed that educational attainment and age of the returnees made the first and the second largest contributions in predicting wage-employment in the positive and negative directions with beta coefficients (β = 0.985; and β = |-0.611| respectively at (p ≤ 0.000) level of significance. A notable proportion of Ethiopian returnees deemed to be unemployed and not engaged in any urban livelihood activities and deprived of enjoying the potential benefits obtained from self-employment and wage-employment activities in the study area.